Predição da composição corporal de ovinos deslanados por meio do corte das costelas 9-10-11ª (SEÇÃO HH) - Sousa, Amanda da Rocha (2017)
The goal of this study was to develop equations to predict the chemical composition of the carcass and the empty body (EB) of sheared sheep by cutting of the 9th to 11th rib section (HH section). The database (n = 171) was obtained from five studies made with 133 noncastrated males, 26 castrated males and 12 females, of which 58 were Santa Inês (SI), 74 Morada Nova (MN) and 39 of the Brazilian Somali (BS) breed. The right half carcass and the HH section of the left half carcass were analyzed for water, crude protein (CP %), ether extract (EE %) and energy (EN Mcal/kg). Remaining body components were also analyzed for the chemical composition of the EB. A stepwise procedure was used to determine the inclusion of the variables in the regression models. The variables included were water (Water H %), protein (CPH %), ether extract (EEH %) and energy (ENH %) from the HH section, carcass dressing (CD %), hot carcass weight (HCW kg), empty Body weight (EBW kg), organs plus viscera (OV %EBW) and visceral fat (VF %EBW). The contents of Water ,EE and EN in the carcass and in the EB were satisfactorily estimated by section HH, but there was no precision in the estimation of protein contents. Breed and sex influenced the contents of Water, EE and EN in the carcass and the contents of CP, EE and EN in the EB. The inclusion of new variables by the stepwise procedure promoted better fit in the equations. The equations obtained in the EB for non-castrated males were: EE (%): Santa Inês = - 9,89 (± 3,03) + 0,38 (± 0,06) x EEH – 0,24 (± 0,10) x OV + 0,90 (± 0,32) x VF (R2 = 0,88; MSE = 1,38), Morada Nova = 6,29 (± 1,47) + 0,52 (± 0,03) x EEH – 0,26 (± 0,09) x OV + 0,44 (± 0,08) x VF (R2 = 0,89; EQM = 1,72), and Brazilian Somali = 7,14 (± 3,92) + 0,49 (± 0,05) x EEH – 0,14 (± 0,23) x OV + 1,04 (± 0,20) x VF (R2 = 0,88; MSE = 2,56); for water (%): 79,49 (± 0,52) - 5,15 (± 0,19) x ENH - 0,34 (± 0,06) x VF (R2 = 0,84; MSE = 3,15) and for EN (Mcal/kg): Santa Inês = 1,25 (± 0,07) + 0,02 (± 0,005) x EEH + 0,21 (± 0,03) x VF (R2 = 0,82; MSE = 0,01), Morada Nova = 1,12 (± 0,06) + 0,05 (± 0,004) x EEH + 0,04 (± 0,01) x VF (R2 = 0,84; MSE = 0,02) and Brazilian Somali = 1,34 (± 0,11) + 0,04 (± 0,004) x EEH + 0,08 (± 0,02) x VF (R2 = 0,87; MSE = 0,02). The results confirm the hypothesis that the HH section can be used to accurately estimate the chemical composition in EE, water and EN of carcass and EB of sheared sheep. However, more studies should be performed to determine the accuracy in the prediction of CP content.